Pengaruh CR, DER, dan ROA terhadap Nilai Perusahaan pada PT Jasa Marga Tbk Tahun 2010-2019 - Wildan Dzulhijar; Leni Nur Pratiwi; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
This study aims to analyze the effect of current ratio, the ratio of debt to equity, and the ratio of the rate of return on assets to firm value at PT jasa marga (PERSERO) Tbk in 2010-2019. This study uses multiple linear regression statistical methods. The independent variables used in this study are current ratio (CR), debt to Equity (DER), and return on assets (ROA) while the dependent variable is price to book value (PBV) which is a proxy for firm value. The results obtained indicate that simultaneously the current ratio, debt to equity ratio and asset return ratio variables have a significant effect on firm value. Then partially current ratio and assets return ratio variables have no significant effect on firm value while debt to equity ratio has a negative significant effect on firm value.